Analisis Capaian Simulasi Pengurangan Kumuh Melalui Kegiatan Penanganan Skala Kawasan Pada Kawasan 29 Ilir Kota Palembang - Alkausari, Bintang; Aminuddin, Kiagus Muhammad; Usman, Arie Putra; Umari, Zuul Fitriana; Jimmyanto, Hendrik (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
This study examines the effectiveness of slum reduction simulation through a region-based intervention strategy in the 29 Ilir settlement, Palembang City. This research differs from previous studies by simulating slum reduction with a measurable quantitative approach for each sectoral aspect. The analytical descriptive approach method was used to integrate primary data from field surveys, namely the seven Slum Aspects (Aspek Kekumuhan). The data analysis process utilized scoring to determine the severity level of the settlement. The research findings from the simulation highlight that interventions targeting environmental infrastructure—especially road improvements and fire protection systems—have the most substantial impact on slum reduction. This result underscores the effectiveness of a region-based approach in accelerating the improvement of substandard urban settlements. To ensure the long-term sustainability of the improved conditions, strategic follow-up measures are essential as part of a preventive and integrated urban development framework.